International books in print (München ; New York : Saur)
Catalog of English-language books published in Africa, Asia, Australia, Canada, Continental Europe, Latin America, New Zealand, Australasia, and Ireland.
Accompanied by manual.
Description based on: 2nd CD-ROM ed. (1992); title from disc label.
System requirements: IBM PC AT PS/2 or compatible; 640 kBytes RAM; MS-DOS version 3.1 or higher; hard disk drive; CD-ROM player; MS-DOS CD-ROM Extensions (MSCDEX).
SERBIB/SERLOC merged record
Keywords: English imprints -- Bibliography -- Databases